Professionalism and associated factors among nurses working in Hawassa city public hospital, Sidama, Ethiopia - Abebe Boe, Eyerusalem; Mekonnen, Shiwangizaw; Fako, Thomas; Aschale Wale, Mastewal; Tade, Meku; Tsega Chekol, Aklile (Frontiers in Medicine, 2024)
The foundation of the global healthcare system is nurses, and professionalism in nursing is a basic idea that helps patients, organizations, and people. Studies that have been published in Ethiopia, though, are limited, out-of-date, and poorly documented, especially when it comes to the study setting. Because of this, this study aimed to close a knowledge gap on the level of professionalism in public hospitals in Sidama, Ethiopia.Objective: To assess professionalism and associated factors among nurses working in Hawassa City Public Hospitals, Hawassa, Ethiopia.Public Hospital from June to July 2022. A computer-generated simple random sampling technique was used to select 413 study participants. The level of professionalism was assessed through a self-administered questionnaire, using the guidelines of the Registered Nurses Association of Ontario. All the loaded data using Epi-data version 4.6 was exported to a statistical package for social science. An ordinal logistic regression analysis was used to identify the associations between the outcome and predictor variables. The statistical significance of the factors influencing the outcome variable was declared in multivariate logistic regression analysis using an adjusted odds ratio at a 95% confidence interval with a p-value <0.05.Results: A total of 405 nurses participated in the study, with a response rate of 98%. Of the total, participants more than half were females (55.3%). The level of professionalism was found to a moderate level. There was a strong link between completing their degree in a governmental institution, being part of a professional organization, serving for several years, and having a BSc or above qualification with a moderate level of professionalism.We found a moderate level of professionalism among nurses working in the study setting. This suggests that the Regional Health Bureau should collaborate with other responsible bodies to develop various opportunities for nursing staff to increase their professionalism. The minister of health should be focused on private college nurses, nurses lacking the association, and the qualification of the profession.